Barriers to and facilitators of pet grooming among clients served by a subsidized grooming service program - McDonald, Shelby E.; Doherty, Colleen; Sweeney, Jessica; Kisiel, Lisa; Matijczak, Angela; Niestat, Laura; Gupta, Maya (Frontiers in Veterinary Science, 2022)
Grooming is an important aspect of basic hygiene care for most companion animals. The consequences of not receiving routine grooming care can pose significant risks to animals' health and wellbeing. The current study examined barriers and facilitators of maintaining pets' grooming needs among clients of a subsidized grooming service program in New York City (N = 167), as well as the impact of a tailored nail-trimming demonstration on clients' confidence trimming pets' nails. Ninety-two percent of the sample reported experiencing at least one barrier to maintaining their pet's grooming (e.g., income, transportation) and nearly half (46%) experienced three or more barriers to providing grooming. Ninety-one percent endorsed that at least one supply/support (e.g., brush/comb, behavioral support) would be beneficial in maintaining their pet's grooming needs at home and more than half reported that three or more supplies/services would be beneficial. Differences in the prevalence of specific barriers to grooming were found across income groups, service locations, and service settings. Clients who received nail-trimming demonstrations, on average, reported statistically significant increases in confidence trimming nails following their appointment. We discuss the implications of these findings for improving animal welfare and veterinary professionals' capacity for preventing grooming-related omissions of care and increasing communities' capacity to support pet owners' access to essential pet care supplies and supports. Future research is needed to determine (a) how and for whom grooming demonstrations and subsidized services are most effective, (b) whether an increase in pet owner confidence following nail trimming demonstrations is associated with maintaining nail trimming at home over time, and (c) whether providing clients with supplies and supports is an effective way of preventing and/or ameliorating future grooming-related omissions of care and hygiene-related health concerns observed by veterinarians, animal control professionals, shelter staff, and law enforcement.